SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAN PENGARUHNYA TERDADAP EFEKTIFITAS KERJA ORGANISASI PEMERINTAH DAERAH KABUPATEN MERAUKE - Ansar Ansar (Gema Kampus IISIP YAPIS Biak, 2021)
Performance accountability of local government instance in implementation as be come important purpose to make good governance and clean goverenment of local government. The process between for apprases organization ferpormance that is pass trough implementation of reports performance accountability system of local government in task and function implementation. The data technique is used statistics method whith SPSS for windows. Data analysis used multiple linier regression. This research aim to know about influence of performance accountability system of government toward organization effetive of Merauke Government Regency. The research result show that accountability system as independent variable meaningful for organization works effetive dependent varable. From seven independent variable of analysis there are five variabels haven influential toward organization works effective of Merauke Government Regencyat of trust worthy level at 95% (a=5%) and show by value of F count >F table, i.e visi and mission, strategic planning, butgetting, performance assisment and performance evaluation, but there are two variabels is not influential i.e program and activity implementation. The variabels butgetting have the most dominand influential toward oraganizatin works effective by regression coefficient of 0,565 follow whith performance evaluatuion by coefficient regression of 0,472 and vision and mission by coefficient regression of 0,410 of other independent variable.